Ammonia oxidation and denitrification in a bio-anode single-chambered microbial electrolysis cell. (August 2020) - Zheng, Decong; Gu, Wenzhi; Zhou, Qinmao; Zhang, Lixia; Wei, Cuicui; Yang, Qingzhuoma; Li, Daping
Highlights: Anodic ammonia oxidation and denitrification were realized in this system. The nitrogen removal was coupled with sulfate-reduction at −300 and −400 mV. Denitrifying and sulfate-reducing were the main functional bacteria at the anode. Carbon and nitrogen could be simultaneously removed at a suitable anodic potential. Abstract: In this study, anodic ammonia oxidation and denitrification were performed in single-chamber bioelectrochemical systems at a wide range of anodic potentials (−400 to +400 mV) versus Ag/AgCl. The low coulombic efficiencies (~30.84%) in reactors were mainly due to electrons being transferred to atmospheric oxygen through the electrode and reversal of the electrode. The removal efficiencies of acetate, ammonia, and total nitrogen were 100%, 100%, and 40.44% at +200 mV and 100%, 100%, and 50.24% at −200 mV, respectively. The nitrogen-removal mechanisms were nitrogen respiration/nitrate reduction at +200 mV and denitrification at −200 mV, and ammonia oxidation occurred by coupling with sulfate-reducing at −300 and −400 mV. Thauera, Comamonas, Alicycliphilus, Nitrosomonas, Desulforhabdus, Dethiosulfatibacter, and Desulfomicrobium were the dominant genera at the anode which participated in the nitrification/denitrification or sulfate-reducing processes. In summary, ammonia oxidation and denitrification could be coupled with carbon-removal or sulfur-reduction using a bio-anode with a suitable anodic potential.